PENERAPAN FINGER PRINT DALAM MENINGKATKAN DISIPLIN KERJA PEGAWAI DI KANTOR DINAS KEPEMUDAAN DAN OLAHRAGA KOTA PALEMBANG - Deffi Haryani (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The goal to be achieved in this study is to analyze in depth the application of finger print in improving employee work discipline at the Palembang City Youth and Sports Service Office. This type of research is descriptive qualitative, data collection techniques by means of observation, interviews, and documentation. The data obtained was analyzed by means of data reduction, data presentation, and conclusion drawing. While testing the validity of the data is done by persistence and observation and triangulation. The triangulation used in this research is technical triangulation. The results of the study show that the application of finger print in improving employee work discipline at the Palembang City Youth and Sports Service Office has been carried out well, this is because employees have carried out their responsibilities very well, and their employees are able to adapt well. This can be seen from the results of interviews with the Head of Service, Secretary of Service, Head of Umpeg Subdivision, Umpeg Staff in the field of finger print and the results of observations made by the researchers stated that the indicators the author used had been implemented so that it made the application of finger print effective and efficient.